A multi-criteria decision making method for urban flood resilience evaluation with hybrid uncertainties. (May 2019) - Li, Zongmin; Zhang, Xinxin; Ma, Yanfang; Feng, Cuiying; Hajiyev, Asaf
Abstract: Urbanization and climate change have increased the frequency of damaging urban floods. While some urban floods are inevitable, it is critical to ensure urban flood resilience to minimize flood losses. This paper develops an urban flood resilience evaluation system that can provide guidance for municipal decision makers. This study first builds a comprehensive flood resilience evaluation system with the whole period of the disaster cycle that covers the resistance capacity before a flood, the coping and recovery capacities during a flood, and the adaptive capacity after a flood. The proposed evaluation system includes hybrid uncertain information that involves hesitant fuzzy judgements from experts and random data. Then, to conquer the weighting difficulty, a maximum consensus model for experts' weights is proposed. After that, the traditional VIKOR method is expanded to aggregate all crisp, random and hesitant fuzzy information, so that, the aggregation method is more adaptive to hybrid uncertain environment. In addition, the proposed method is applied to 5 south-eastern coastal cities in P.R.China. Practical managerial suggestions are put forward to increase urban flood resilience in these cities. Finally, the sensitivity analysis for the results and the comparison analysis are conducted.